KERAGAAN PRODUKSI, KETERSEDIAAN BERAS, DAN TRANSFORMASI LAHAN PADI INDONESIA - Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2008)
The provisions of food in order to fulfill the requirement for humankind could be followed through the implementation of the process of agricultural production. However, the food requirement could only be fulfilled self-sufficiently if food supplies were higher than the total consumption. The trend of the Indonesian rice production rises the problem that immediately must be overcome. This was caused by increasing consumption continuously resulting from the increase in population growth. Besides that, the other problems are rice field transformation, from rice field to industrial and residential area.